DISTRIBUTION OF CARBON STARS IN THE GALAXY - Eglitis, I.; Sokolova, A. (Одеські астрономічні публікації, 2018)
A search for new faint carbon (C) stars in the Polar region δ > 55o has been accomplished by obtaining objective prism spectra in the near infrared 550 – 900 nm on images of CCD camera of Baldone Schmidt telescope of Astrophysical observatory. The positions of stars having color indices (J – K) > 1.3 mag in Two Micron All Sky Infrared Survey (2MASS) were selected to pick out suspicious carbon stars. Our survey is limited in brightness by J < 10 mag. 24 new carbon stars were found and their characteristics obtained. The correlative relation between Teff and spectral gradient [757 – 685] was confirmed. Such characteristics as Teff, distance from the Sun, absolute Mk were obtained for newly discovered carbon stars.